2021
DOI: 10.3390/catal11040434
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Derived from Agricultural Wastes as a Means of Facilitating the Degradation of Azo Dyes by Sulfides

Abstract: Dyes are common contaminants, some of which are teratogenic, carcinogenic, and causative of ecological damage, and dye wastewater often contains toxic sulfides. Biochar has been widely used for the adsorption and catalysis degradation of pollutants, including dyes and sulfides, due to its abundant surface functional groups and large specific surface area. Therefore, the simultaneous treatment of dyes and sulfides with biochar may be a feasible, effective, and novel solution. This study sought to utilize low-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…pH levels of RWSB and SSB in this study are comparable or similar to previous studies by Angın (2013), Ferreira et al (2019 and Reza et al (2020). On the other hand, Han et al (2021) reported that the low pH of biochar can be relatively in uence, because of the hydrogen H + ions engaged the biochar adsorption pour sites. Biochar with higher pH has more potential for use as soil conditioner that reduces heavy metal contaminants.…”
Section: Thermogravimetric Analysissupporting
confidence: 90%
“…pH levels of RWSB and SSB in this study are comparable or similar to previous studies by Angın (2013), Ferreira et al (2019 and Reza et al (2020). On the other hand, Han et al (2021) reported that the low pH of biochar can be relatively in uence, because of the hydrogen H + ions engaged the biochar adsorption pour sites. Biochar with higher pH has more potential for use as soil conditioner that reduces heavy metal contaminants.…”
Section: Thermogravimetric Analysissupporting
confidence: 90%
“…27,28 Toxic sulde contaminants are also present in dye wastewater, as they are used as dyeing auxiliaries with azo dyes; thus, they are also common reducing agents in the natural environment. 29 They can moderate azo dye contaminants in wastewater, but the reaction rate is very slow. Therefore, BC of different particle sizes was used to mediate the redox reaction between azo dyes and suldes in the present study.…”
Section: Bc-mediated Degradation Of Mo By Suldementioning
confidence: 99%
“…Anion dyes are widely used in the dyeing process due to their simple synthetic process, low cost, and better staining performance [3,4]. During the process of anionic dyeing, the fabric needs to be washed several times to improve its dyeing fastness, resulting in the generation of a large amount of anionic dye wastewater [5], causing oxygen deficiency and jeopardizing the viability of aquatic animals and plants [6,7].…”
Section: Introductionmentioning
confidence: 99%